Childhood Psychological Maltreatment, Mindful Awareness, Self-Transcendence, and Mental Well-Being in Emerging Adults - Arslan, Gökmen; Kabasakal, Zekavet; Taş, Besra; Taş, Besra (SAGE Publications Inc., 2024)
Psychological maltreatment is a severe form of abuse that can have a significant negative impact on an individual’s mental health and well-being. Examining the factors that reduce the negative effects of child maltreatment on the outcomes can, hence, contribute to the development of effective prevention and intervention strategies, providing resources and support for families, early detection, and education for parents and caregivers. The present study aimed to explore the mediating role of mindful awareness and self-transcendence in the association between childhood psychological maltreatment and mental well-being among Turkish emerging adults. The study sample consisted of 422 emerging adults enrolled in a state university in Türkiye (with 65% of female). Participants ranged in age from 18 to 29 years, with a mean age of 20.94 years (SD = 1.86). The present study found that psychological maltreatment was not only directly associated with lower levels of mindful awareness and self-transcendence, but also indirectly associated with poorer mental well-being through the mediating effects of these variables. The study suggests that childhood psychological maltreatment is a significant risk factor for mental well-being among emerging adults, and highlights the importance of promoting the development of mindful awareness and self-transcendence in preventions and interventions aimed at improving mental well-being. By cultivating these positive psychology states, emerging adults may be better equipped to overcome the negative effects of psychological maltreatment.
Keywords: Mental well-being; Mindful awareness; Positive psychology; Psychological maltreatment; Self-transcendence